2011
DOI: 10.4028/www.scientific.net/amr.347-353.1117
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Coal Hybrid Thermal Power Generation in China

Abstract: Coal is presently the largest source of electricity in China, with the increasing demand for electricity, the problems of environment pollution become more and more severe. In order to solve the problems, all options for power generation by new and renewable energies are enjoying growing attention in recent years. China has abundant solar energy resources and large wasteland areas, which makes China an ideal country for solar thermal power generation development. However, its present higher costs for China mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Hou H. et al [10] found that the specific fuel consumption of the solar-assisted hybrid power plant was lower than the reference thermal power plant, and they found that the specific fuel consumption decreased further with the increase in solar radiation value. Suresh et al [11] have shown that using solar energy to heat the feedwater entering the high-pressure preheaters produces the best results in terms of fuel economy and reduction of carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Hou H. et al [10] found that the specific fuel consumption of the solar-assisted hybrid power plant was lower than the reference thermal power plant, and they found that the specific fuel consumption decreased further with the increase in solar radiation value. Suresh et al [11] have shown that using solar energy to heat the feedwater entering the high-pressure preheaters produces the best results in terms of fuel economy and reduction of carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the solar thermal to electricity conversion efficiencies of the solar hybrid power plant are higher than those of a solar-only power plant with solar heat input at the same temperature [10,11]. Replacement of higher grade extraction steam facilitates better thermal performance and efficiency [12]. Hong et al [13] investigated the exergy destruction of a solar-coal hybrid power plant using an energy-utilization diagram (EUD) methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Hou u. a. [62] estudia varios diseños de planta híbrida para el caso de una planta de carbón de 150 M W . Para cada caso se determina la potencia extra que se puede generar en función de la potencia solar instalada mediante expresiones polinómicas cuyos coeficientes se han obtenido de las referencias [43] y [98].…”
Section: Se Calcula El Ciclo Combinadounclassified